AKTIVITAS ANTIMIKROBA Lactobacillus plantarum 1 YANG DIISOLASI DARI INDUSTRI PENGOLAHAN PATI SAGU TERHADAP BAKTERI PATOGEN Escherichia coli FNCC-19 DAN Staphylococcus aureus FNCC-15 - Noni Afriani; Yusmarini Yusmarini; Usman Pato (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was todetermined and measure the antimicrobial activity of Lactobacillus plantarum 1 isolated from sago starch processing industry against pathogenic bacteria Escherichia coli FNCC-15 and Staphylococcus aureusFNCC-19. The research was carried out experimentally  using Completely RandomizedDesign (CRD) with four as treatments and four replications. Antimicrobial activity was tested using the well diffusion method and the paper disc diffusion method. Result of analysis of variance showed that the antimicrobial activity of lactic acid bacteria isolates and cell-free supernatant of bacteriaStaphylococcus aureus FNCC-15 and Escherichia coli FNCC-19 were significantly different (P<0.05%).  T test result showed that the inhibition zone produced acid between bacteria isolates to cell-free supernatant were significantly different (P<0.05%).The average diameter inhibition zone of lactic acid bacteria isolated againstStaphylococcus aureus FNCC-15 were from 6.10 to 8.08 mm. The average diameter inhibition zone of lactic acid bacteria isolated againstEscherichia coli FNCC-19 were from 6.80 to 9.20 mm. The average diameter cell-free supernatant inhibition zone against bacteria Staphylococcus aureus FNCC-15 were from 1.22 to 2.41 mm and inhibition cell-free supernatant against Escherichia coli FNCC-19 ranged from 2.06 to 3.50 mm. The results of this study indicate that the isolates of Lactobacillus plantarum 1 RN2-12112 and the supernatant had greater antimicrobial activity than isolates of Lactobacillus plantarum 1RN2-53. Keywords: Lactic acid, Antimicrobials, Lactobacillus plantarum 1,Supernatant